QUALIDADE NA PRODUÇÃO DE REFEIÇÕES EM RESTAURANTES DO TIPO SELF-SERVICE - Marlene Azevedo Magalhães Monteiro; Jéssica Agda do Carmo Fróes; Rafaela Barros Romano Fontes; Rita de Cássia Ribeiro (Demetra, 2015)
The economic, social and cultural transformations the world has been going through have entailed an increasing search for “eating out”. In Brazil, 35% of the meals are eaten out and the establishments patrons most attend to include “self-service cafeteria” restaurants. These rank second in the list of meal production services (MPS) with the highest occurrence of foodborne diseases (FBD). In this context, this study aimed to analyze the hygiene and health quality of self-service cafeteria restaurants in the Center-South of the city of Belo Horizonte, Minas Gerais state, Brazil. Therefore, a checklist was applied at ten MPS, elaborated in accordance with Resolutions 275/2002 and 216/2004, aimed at checking the level of “non-compliance” of the establishments. According to the results, the restaurants were classified in groups according to the criteria established in RDC 275/2002. The percentage of compliance among restaurants ranged from 29.63% to 90.91%, at an average of 68.19% (±19.12%). Only three restaurants fit into Group I, and most were classified in Group II. In conclusion, great discrepancy was found among the restaurants assessed, which indicates the need for greater surveillance of the MPS. In addition, the presence of a technician in charge, graduated in the field of food handling and best practices, has positively influenced greater compliance to the legislation. The results also demonstrate the insufficient quality of the services that the restaurants offer and suggest the need for more surveillance. DOI: http://dx.doi.org/10.12957/demetra.2014.13375